Carbon balance in grapevines (Vitis vinifera L.): effect of environment, cultivar and phenology on carbon gain, losses and allocation. (6th April 2022) - Hernández‐Montes, E.; Escalona, J.M.; Tomás, M.; Martorell, S.; Bota, J.; Tortosa, I.; Medrano, H.
Abstract: Background and Aims: Measuring the carbon assimilation and respiration during vine phenology can provide an understanding of the dynamics of carbon fluxes from different organs and their relationship. Most field studies to date do not consider the respiratory losses of different plant organs and their variability under environmental, genetic and phenological changes. The aim of this study was to investigate the effect of genotype and water regime on carbon assimilation, respiration and allocation during vine phenology. Methods and Results: Field trials were carried out during 2013 and 2014 to study the effect of genotype and water status on carbon assimilation, respiratory losses from leaves, shoots, fruits and roots during the vine phenological cycle, and on biomass production. Carbon respiration varied during plant phenology and represented a significant proportion of the total vine carbon assimilation. The integrated carbon respiratory loss in leaves, fruits and roots was greater in irrigated vines than in non‐irrigated vines. Tempranillo recorded the highest carbon assimilation, leaf and stem respiration, as well as the highest above‐ground biomass. Garnacha showed a higher root respiration loss and allocated more biomass to the permanent organs. Accumulation of above‐ground biomass was influenced by plant carbon budgets during the growing season. Conclusions: Vine phenology, cultivar and plant water status affected carbon assimilation, carbon loss and carbon allocation. Non‐irrigated vines had a higher respiratory carbon loss in respect to the total carbon assimilation by photosynthesis. Above‐ and below‐ground carbon fluxes were coupled during vine phenology. Significance of the Study: The present work illustrates the importance of respiratory processes on the carbon balance and the relationship among different carbon balance components during vine phenology.